ダイ9ジ ナンキョク チイキ カンソク エットウタイ ウチュウセン ブモン ホウコク ウチュウセン チュウセイシ レンゾク カンソク ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 須田, 友重; スダ, トモシゲ; 小玉, 正弘; コダマ, マサヒロ; SUDA, Tomoshige; KODAMA, Masahiro (国立極地研究所, 1971)
P(論文) From February 1968 to January 1969, cosmic ray nucleonic component was observed at Syowa Station, Antarctica (69°00'S, 39°35'E), using a duplicate set of 5-NM-64 super neutron monitor with a multiplicity meter. Almost complete observations were achieved except the lack of 4 consecutive days for one monitor. The mean multiplicity of the monitor is 1.42 ± 0.03 and is in agreement with the value of the standard 6-NM-64 monitor obtained by HATTON, et al. The mean life time of neutrons in the pile is found to be 547 ± ^<123>_<85>μs which is a little longer than that in the 6-NM-64 monitor. These results come from the pile which was constructed as a single pile consisting of 10-NM-64 neutron counters. The annual change of neutron intensity covers 9.0% in range, showing the maximum in April and the minimum in November, with larger disturbance in the later half year than in the former half. The multiplicity dependence of the barometric pressure effect and Forbush decreases are surveyed briefly. Using the data from three large Forbush decreases, the relation between the multiplicity events and their corresponding primary rigidities is discussed by comparing the latitude dependence of the amount of decrease. Descriptions and data of the solar cosmic ray event of November 18, 1968 are also given. departmental bulletin paper